PENGGUNAAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA - Faridayati Faridayati (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
This study uses the role playing method in Indonesian language lessons. The objectives of this study are (1) to improve the speaking skills of the fifth C grade students of SD Negeri 104214Kedai Durian (2) applying the use of role playing methods to Indonesian language lessons (3) helping students to understand the subject matter. The method used in this study is classroom action research which is used in the fifth C grade which amounts to 24 students. Based on the analysis of the data obtained that the initial observations of 24 students obtained that 6 students which 25% who were able to speak well, and as many as 18 students 75% who did not speak well with an average value of 12. In the first cycle there are 10 students that 41.66% who have been able to speak and as many as 14 students that 58.34% who have not spoken properly with an average score of 12.87. Then in the second cycle, students 'speaking skills increased to 18 people 75% who were able to speak with an average of 13.95%. Thus it can be concluded that the use of role playing methods can improve students' speaking skills in drama lessons in Indonesian language lesson in the fifth C Junior High School. Therefore teachers need to improve their teaching skills by using the role playing method as one of the efforts made to improve students' speaking skills in Indonesian language lessons.